Analysis of Think Pair Share Implementation on Students’ Communication Skills at The Second Grade of Pondok Pesantren Ashhabul Yamin Lasi - Chelsy Hanna Primadona; Hilma Pami Putri; Irwandi Irwandi; Loli Safitri (Pusdikra-Publishing.com, 2024)
This study aims to evaluate the application of the Think-Pair-Share model in improving students' communication skills at Pondok Pesantren Ashaabul Yamin. Although many schools apply this model, this study found some errors in its application in the school. One of them is that the teacher did not follow the correct sequence and did not have a significant impact on students' communication skills. The study used a qualitative descriptive method with the participation of 1 teacher and 31 students. Data was collected through observation with 11 activities that reflect the application of Think-Pair-Share to students' communication skills. The results showed that although the lesson plan described the application of Think-Pair-Share as a learning model, the teacher did not follow the plan. In addition, the teacher also did not adhere to the correct indicators, as seen from the observation data. However, at the sharing stage, the teacher succeeded in improving students' communication skills, especially when students shared the results of their group discussions in front of the class.